Youth in Chile: Gender Differences in Attaining Adult Social Roles - Felipe Tello-Navarro; Carlos Mellado; Verónica Gómez-Urrutia (RIMCIS)
This article analyzes differences in life trajectories in Chilean young people (men and women) entering adulthood (ages 18-29). Using data from the Tenth National Survey on Youth and latent class analysis, we identify seven types of transition to adult life based on socio-demographic variables that the literature establishes as markers of adulthood, such as financial independence and having children and being head of household among others. Our results show that a reduced proportion of young people have all the social markers of adulthood, suggesting that most youngsters do not fully assume adult roles until they reach the fourth decade of their lives. In a similar vein, data show that most youngsters aged 18 to 29 live with their parents and/or are still enrolled in education. We also identify differences by sex, showing that the roles of women as caregivers of children are important in the diversification of young people's life trajectories. Such a transformation in Chile’s socio-demographic structure has a direct impact on key public policy issues, including young people’s access to housing, falling fertility rates and the adequate age of retirement.